Keanekaragaman dan Hubungan Kekerabatan Pisang (Musaceae) di Kota Bengkulu, Provinsi Bengkulu - Evelyne Riandini; Nur Fitria; M Reicky Setiawan (Biota, 2018)
This study was to determine the diversity and banana phylogeny (Musaceae) in Bengkulu City, Bengkulu Province. The results of this study are expected to be an information material for development to achieve improvements in banana varieties / cultivars. Collection of exploration study data in selected Bengkulu City, namely 3 Districts of Muara Bangkahulu, Sungai Serut, and Teluk Segara. The location of specimen collection consists of wild and cultivated plants in the yard and a community garden in the city of Bengkulu. Morphological data were compiled based on observations of morphological characters from specimens in the field, characters adapted from banana descriptors. Morphological data were compiled based on observations of specimens, the results of morphological characters were analyzed to form fenogram to see phylogeny, using the NTSYS-pc 2.02 program. 22 collections and 10 varieties of bananas (Musaceae), wild bananas and cultivation by the community were found in 3 sub-districts of Muara Bangkahulu, Sungai Serut, and Teluk Segara. Cultivated bananas that are planted in general, the community planted in the home yard for home-based commodities. The relationship between wild bananas (Musaceae) and cultivation in the city of Bengkulu, divided into two main groups, namely group A, namely the type of Musa acuminata Colla and group B is the type of Musa acuminata x Musa balbisiana. Both of these groups have similarity coefficient values of phylogeny between 0.45 to 0.60.